2002
DOI: 10.1097/00007890-200201150-00004
|View full text |Cite
|
Sign up to set email alerts
|

Pig Hematopoietic Cell Chimerism in Baboons Conditioned With a Nonmyeloablative Regimen and Cd154 Blockade1

Abstract: These results suggest that there is no absolute barrier to pig hematopoietic cell engraftment in primates, and that this may be facilitated if the return of anti-Gal IgG can be prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 39 publications
1
47
2
Order By: Relevance
“…Subsequent studies attempted to increase engraftment by raising the dose of progenitor cells administered through the use of cytokine-mobilized PBPC, achieving doses as high as 2–4 × 10 10 cells/kg following mobilization and pheresis [62,63]. Even after administration of these enormous doses of pig cells, they were generally detected in the baboon circulation for only 2–5 days, although one animal demonstrated a second appearance of pig cells in the circulation on days 16–21 [64].…”
Section: Current Status Of Tolerance Induction In Primatesmentioning
confidence: 99%
“…Subsequent studies attempted to increase engraftment by raising the dose of progenitor cells administered through the use of cytokine-mobilized PBPC, achieving doses as high as 2–4 × 10 10 cells/kg following mobilization and pheresis [62,63]. Even after administration of these enormous doses of pig cells, they were generally detected in the baboon circulation for only 2–5 days, although one animal demonstrated a second appearance of pig cells in the circulation on days 16–21 [64].…”
Section: Current Status Of Tolerance Induction In Primatesmentioning
confidence: 99%
“…Newly developing B cells could not be found in spleens of late chimeras, suggesting deletion and/or receptor editing [117]. Still, engraftment barriers across species are difficult and might be overcome via retroviral gene therapy [104, 118]. …”
Section: A Future For Molecular Chimerism or Xenograft Tolerance?mentioning
confidence: 99%
“…[12][13][14] Based on experience of allotransplantation across the ABO blood group barrier (reviewed in Ref 15), particularly by Alexandre and colleagues, 16 in which depletion of Abs at the time of the organ transplant resulted in accommodation (graft survival in the presence of specific anti-donor Ab and complement), enormous efforts were expended to achieve accommodation by the initial immunoadsorption of anti-Gal Abs using immunoaffinity columns of various Gal-glycoconjugates. [17][18][19][20][21][22][23][24][25] Although anti-Gal Ab could be depleted completely by a course of plasmapheresis and immunoadsorption over the period of a few days, and although this protected the graft from HAR, return of preformed and/or elicited Ab inevitably led to AHXR (Table 2 and Figure 3). 19,22,26 Despite pharmacologic immunosuppressive therapy, graft survival could not be extended beyond 30 days.…”
Section: Phase Iii: Extracorporeal Immunoadsorption Using Synthetic Gmentioning
confidence: 99%
“…Less morbidity was reported when co-stimulatory blockade was introduced. 21, 24,39 The fact that anti-non-Gal Abs were not adsorbed may have been detrimental, as subsequent in vitro laboratory studies have indicated that anti-non-Gal Abs can result in pig cell lysis. 41 It has recently been demonstrated that anti-non-Gal Abs can be associated with AHXR.…”
Section: Phase V: Continuous "Depletion" or "Neutralization" Of Anti-mentioning
confidence: 99%
See 1 more Smart Citation